Incorporating hip-hop composition into the traditional middle school band setting - Rodriguez, Guillermo (Kansas State University, 2020)
In this report, I describe a lesson in which students learned ways to create modern hip-hop styled compositions that would connect to a traditional example in their band method book. Through composition, students were able to discuss larger concepts that would not come by naturally by only looking at sheet music and not creating their own music. After their compositions, students were able to reflect on music they have played and relate what composers wrote to make a piece into music. Through this program I have developed into a more well-rounded teacher by learning more practices for my classrooms, how to continually reflect on a daily basis to improve and learning more deeply about pedagogical philosophies that help me further define my own teaching philosophy. I learned the following practices: use of composition in any ensemble level, technique in instrument pedagogy, and learning more literature by looking at the history and development of wind band literature. My ability and knowledge as a band director have improved during my time in this program. All the tools mentioned have already made me and my students a better musician and learner. The skills I gained from lessons on organization and delegation have helped give ownership to my students while relieving duties from daily tasks.
Keywords: Music composition; Hip-hop in band; Middle school band